Protocols for uterine preparation for implantation - Granot, Irit (Henry Stewart Talks, 2019)
Implantation as the rate-limiting step for successful IVF treatment, Inadequate uterine receptivity & implantation failures, Endometrial dating methods in routine IVF treatments, Treatment methods used to increase endometrial receptivity, Molecular mechanism by which injury increases endometrium receptivity, Effect of injury-induced DCs and macrophages on implantation-associated genes by endometrial cells, Implications of the development of a protocol treatment that improves endometrial receptivity